Penggunaan Metode Discovery untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPA di Mi Ma’arif NU Ajibarang Kulon - Isti’anataun, Isti’anataun (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
This research is motivated by the low learning outcomes of science class 5 subjects. This is because students seem less active in teaching and learning activities in class, there is no enthusiasm of students to learn, lack of enthusiasm in asking teachers. Many students consider science subjects to be difficult to understand, and many students are busy by themselves when the teacher explains science material in front of the class. The reason for these problems is that when teachers' learning activities dominate more than the students themselves. The purpose of conducting this research is that the learning outcomes of 5th grade students at MI Ma'arif NU Ajibarang Kulon, especially in science subjects using discovery methods can improve their learning outcomes. The object of this study was 5th grade MI Ma'arif NU Ajibarang Kulon students. In the process of collecting data in this research activity using observation, interviews, tests, and documentation. From this study shows that in activities with learning science by using the discovery method can improve learning outcomes of science in class 5 MI Ma'arif NU Ajibarang Kulon, and learning outcomes of science subjects indicated by the value of the results of the initial test, the first cycle test and cycle II has increased in each cycle. In the initial observation activity the number of students above the KKM only reached 41.66%, in the first cycle it rose to 68.18% and in the second cycle it increased again to 90.91%.